Larangan Pernikahan di Bulan Caghai dalam Perspektif Fikih Munakahat (Studi Kasus di Jorong Padang Tongga Nagari Manggopoh Kecamatan Lubuk Basung Kabupaten Agam) - Dila Dia Sari Chan; Ali Rahman (AHKAM, 2026)
The prohibition of marriage during the month of Caghai is a customary tradition that continues to be maintained by the community of Padang Tongga Hamlet, Manggopoh Village, Lubuk Basung Subdistrict, Agam Regency. Although prohibitions against marriage during certain months have been examined in various studies, research specifically analyzing the prohibition of marriage during the month of Caghai from the perspective of fiqh al-munakahat remains limited. This study aimed to analyze the community’s understanding of the prohibition of marriage during the month of Caghai and examine its status from the perspective of fiqh al-munakahat. The study employed a qualitative approach with a case study design. The research informants consisted of alim ulama, niniak mamak, datuak, bundo kanduang, village officials, and community members selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation and were subsequently analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The results showed that most community members viewed the month of Caghai as a month of separation that was considered inauspicious for marriage because this belief had been passed down through generations. However, from the perspective of fiqh al-munakahat, this prohibition has no legal basis in the Qur’an or hadith and therefore does not affect the validity of a marriage as long as its essential elements and requirements are fulfilled. These findings extend the study of Islamic Family Law concerning the relationship between custom (‘urf) and fiqh al-munakahat in the marriage practices of Minangkabau communities. In practical terms, the results can serve as a reference for customary leaders, religious leaders, village authorities, and community members in harmonizing the preservation of custom with the implementation of Islamic law.